An analysis of the effects of the Spanish teams individual and collective performance on winning matches in the 2010 football world cup - Erdil, G.; Bozkurt, S.; Isleyen, C. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In order to deliver cutting edge performance, todays football players need to use their talent and strategy effectively and optimaly. The aim of this study is to analyze and evaluate the technical elements used in the tournaments that led to the victory of the 2010 Football World Cup Champion Spain. Methods Seven DVD's of Spanish team in the 2010 Football World Cup were analyzed by using the Game Breaker Plus by Sports Tech program. Results & Discussion Features of game analysis include: the start and end direction of an attack, the style of scoring a goal, and such 'Key Performance Indicators' (KPI) as resting balls. Conclusion The match analysis has shown, that Spain's team performance plays a dominant role, whereas players individual talents function as a complementary forte.